Sukumari Bhattacharji, Literature in the Vedic Age; Vol. I. The Saṃhitas, Baġchi Indological Series 3, Calcuta, Bagchi & Company, 1984, pp. XXXII + 335. - Laddu, S. D. (Estudios de Asia y África, 1987)
-